Comparative Study of Epidural Ropivacaine 0.75% and Bupivacaine 0.5% with Fentanyl for Elective Caesarean Section in Andhra Pradesh Population: Editor's Note: This article has been retracted as of January 2026 as it is out of scope (Indian Journal of Public Health Research & Development, 2023)
Background: Ropivacaine had clinical advantages over Bupivacaine with respect to cardiac toxicity and motorblock and it was suitable for epidural caecerian section. This study was set-up to compare epidural ropivacainewith fentanyl with Bupivacaine / Fentanyl mixture in LSCS surgeries.Method: Out of 90 patients 45 received 10 mg hyperbaric Bupivacaine with 20 microgram fentanyl and 45 (groupRF) received 15 mg hyperbaric Ropivacaine with 20 microgram fentanyl Hemodynamic parameters sensory andmotor blockade APGAR score were compared in both groups.Results: Demographic profile i.e., Weight, Height BMI Duration of surgery was same in both groups (p>0.001 wasinsignificant) were motor and sensory blockades highly significant (p
Keywords: Bupivacaine, Fentanyl, Ropivacaine, VAS analogue, Hemodynamic